2022
DOI: 10.48550/arxiv.2211.08705
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resource Allocation of Federated Learning for the Metaverse with Mobile Augmented Reality

Abstract: The Metaverse has received much attention recently. Metaverse applications via mobile augmented reality (MAR) require rapid and accurate object detection to mix digital data with the real world. Federated learning (FL) is an intriguing distributed machine learning approach due to its privacy-preserving characteristics. Due to privacy concerns and the limited computation resources on mobile devices, we incorporate FL into MAR systems of the Metaverse to train a model cooperatively. Besides, to balance the trade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Another framework, Metaslicing, groups applications with common functions into MetaInstances, addressing high resource requirements [92]. Zhou et al introduce a federated learning-based resource allocation strategy [93], which optimises the weighted combination of energy consumption, model accuracy, and execution latency, outperforming incumbent benchmarks. Chua et al [94] As highlighted, resource dimensioning in the traditional metaverse optimises computational resources for rendering tasks like 3D graphics, physics simulations, and real-time interactions, ensuring peak performance, scalability, security, cost-efficiency, and future growth.…”
Section: Emotion-aware Resource Dimensioningmentioning
confidence: 99%
“…Another framework, Metaslicing, groups applications with common functions into MetaInstances, addressing high resource requirements [92]. Zhou et al introduce a federated learning-based resource allocation strategy [93], which optimises the weighted combination of energy consumption, model accuracy, and execution latency, outperforming incumbent benchmarks. Chua et al [94] As highlighted, resource dimensioning in the traditional metaverse optimises computational resources for rendering tasks like 3D graphics, physics simulations, and real-time interactions, ensuring peak performance, scalability, security, cost-efficiency, and future growth.…”
Section: Emotion-aware Resource Dimensioningmentioning
confidence: 99%
“…• Applications. Recent studies [58,59] have shown that FL can be broadly applicable in the IoT industry, such as in smart healthcare and smart cities, etc. In addition, FL also helps detect malicious attacks in federated IoT systems.…”
Section: Iot Of Fl4mmentioning
confidence: 99%
“…Some applications seek greater system security, while others seek better model accuracy. Although there are some algorithms and schemes [6,59] proposed to solve the load and resource allocation problems of the metaverse systems, they do not take into account the dynamic cases. The number of system nodes is usually not determined at the time of application deployment, and the allocation of resources should change dynamically as nodes are added or removed.…”
Section: Challengementioning
confidence: 99%